Flood flow reduction via optimization of outlet control structure at Setapak Jaya pond - Rawi, Nor Hayati (2015)
Flooding has been one of the most costly disasters in terms of both property damage and human casualties. Floods cannot be fully controlled if the storage ponds constructed without the outlet control structure. Storage ponds are required to store water during rainy season to control flood. It is can reduce the peak volume of runoff from a catchment which can reduce the frequency and extent of downstream flooding. The main objective of the study is to analyse the flood flow reduction trough outlet control structure geometry optimization at difference scenario using Infoworks ICM model. This case study is conducted at Setapak Jaya Pond which is one of the upstream Sungai Bunus tributaries. There are six scenario combination of 3 number orifices and broad crested weir to identify the lowest peak flow to control the discharge water from Setapak Jaya catchment. Scenario 5 and scenario 3 is the best solution for low flow and scenario 2 for high flow. The result for scenario 5 is 4.559m3/s which the water was discharge trough overflow broad crested weir and closed all the existing orifices with the control gate valve. Outflow for scenario 3 is 9.797m3/s which the water discharge through 2 numbers orifice and rubber dam at 1.5m high mounted on the board crested weir. Scenario 2 is the best flow rates attenuation for 10 ARI is 14.77m3/s ,20 ARI is 21.80m3/s ,50 ARI is 32.90m3/s and 100 year ARI is 42.19m3/s. It was achieved using a combination of 3 nos orifice pipe discharge outlet of 1.0m and an inflatable rubber dam place at various high above the water level. Therefore, scenario 2 is the best solution for Setapak Jaya pond.